Infecção leptospiral assintomática é associada à doença renal canina crônica - Sant’anna, R.; Vieira, A. S.; Oliveira, J.; Lilenbaum, W. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
There are scarce studies associating asymptomatic leptospiral infection with chronic kidney disease (CKD) in dogs, recent research has suggested that in human being asymptomatic renal colonization is a neglected risk for CKD, especially in endemic areas.